2021
DOI: 10.21203/rs.3.rs-888057/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tribocatalytically-activated carbon-based tribofilm formation for wear reduction in alkane environment

Abstract: Minimizing the wear of the surfaces exposed to mechanical shear stresses is an ideal solution to maximizing the lifespan of rotary mechanical parts. In this study, we have discovered the anti-wear capability of a series of metal nitride-copper nanocomposite coatings tested in a liquid hydrocarbon environment. The results indicate substantial reduction of the wear in comparison to the uncoated steel substrate. Analysis of the wear tracks indicates the formation of carbon-based protective films directly at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Additionally, in the evaluation of MoN-Cu and VN-Cu coatings with catalytic properties, dodecane demonstrates the lowest propensity for tribofilm formation among the tested alkanes, while decane and hexadecane display more uniform tribofilm structures [32].…”
Section: 2mentioning
confidence: 96%
See 2 more Smart Citations
“…Additionally, in the evaluation of MoN-Cu and VN-Cu coatings with catalytic properties, dodecane demonstrates the lowest propensity for tribofilm formation among the tested alkanes, while decane and hexadecane display more uniform tribofilm structures [32].…”
Section: 2mentioning
confidence: 96%
“…The study and understanding of the formation and properties of carbon-based tribofilms from hydrogenated alkanes [16] and hydrocarbon-rich environments [15,32] during tribological tests are essential for improving lubrication efficiency, reducing wear, and enhancing the performance and durability of sliding surfaces in various applications. Recent investigations have revealed that longer-chain hydrocarbons, specifically hexadecane, exhibit enhanced tribocatalytic activity and higher reactivity compared to their shorter-chain counterparts.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation